2003
DOI: 10.1016/s0002-9440(10)63822-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hippocampal Insulin-Degrading Enzyme in Late-Onset Alzheimer's Disease Is Associated with the Apolipoprotein E-ε4 Allele

Abstract: Abeta is the major component of amyloid plaques characterizing Alzheimer's disease (AD). Abeta accumulation can be affected by numerous factors including increased rates of production and/or impaired clearance. Insulin-degrading enzyme (IDE) has been implicated as a candidate enzyme responsible for the degradation and clearance of Abeta in the brain. We have previously shown that AD patients exhibit abnormalities in insulin metabolism that are associated with apoliprotein E (APOE) status. The possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
207
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(223 citation statements)
references
References 39 publications
15
207
1
Order By: Relevance
“…3C,D). This is consistent with the results of Cook et al (2003) which found that IDE levels are reduced by up to 50% in ApoE4ϩ human subjects compared with ApoE4Ϫ subjects.…”
Section: Correlation Of Pi3 Kinase (P85) and Ide In Human Brainssupporting
confidence: 93%
“…3C,D). This is consistent with the results of Cook et al (2003) which found that IDE levels are reduced by up to 50% in ApoE4ϩ human subjects compared with ApoE4Ϫ subjects.…”
Section: Correlation Of Pi3 Kinase (P85) and Ide In Human Brainssupporting
confidence: 93%
“…A recent neuroimaging study indicates that Aβ levels are associated with cognitive impairment in non-demented individuals [35]. Furthermore, Alzheimer's disease patients with an APOE ε4 allele exhibit lower levels of IDE in the hippocampus than those without an APOE ε4 allele [36]. It has been suggested that increased Aβ deposition may result both from the decreased expression of IDE in individuals with an APOE ε4 allele and the decreased IDE levels caused by increased use of IDE for insulin regulation in individuals with diabetes, thus leading to higher levels of Alzheimer's disease pathology in participants with both diabetes and APOE [18].…”
Section: Discussionmentioning
confidence: 99%
“…185,186 There are many lines of evidence suggesting IDE dysfunction in AD pathogenesis. For example, levels of IDE are reduced in AD, 187,188 and AD patients may display impaired insulin clearance. 189 Diabetes mellitus is also associated with increased risk for AD, 190,191 IDE haplotypes have an association with plasma Ab1-42 levels, 192 and other metabolic imbalances characteristic of hyperinsulinaemia may impair IDE activity.…”
Section: Ab-degrading Enzymesmentioning
confidence: 99%
“…Furthermore, apoE isoforms may have a modulatory role in IDE expression as APOEe4 carrying AD patients have reduced levels of IDE in the hippocampus and cortex when compared to non-APOEe4 carrying AD patients and controls. 188 Thus, improving IDE metabolism of Ab is of possible therapeutic benefit. Given the parallel decrease in IDE and insulin levels in AD patients, it is possible that insulin may regulate IDE expression.…”
Section: Ab-degrading Enzymesmentioning
confidence: 99%